Magnificent madness, the American lunar quest : creating a contemporary depiction of the lunacy myth : a thesis presented in partial fulfilment of the requirements for the Masters of Design at the College of Creative Arts, Massey University, Wellington, 7 March 2011 - Shields, Ryan (Massey University, 2011)
For many people born in the latter decades of the twentieth century the defining global event was 9/11. For those born in the earlier and mid-decades that moment was the American space race of the 1960s. This project examines the historical and symbolic legacy of that endeavour from a postmodern perspective. In it I investigate how in addition to scientific rationalism, lunacy and madness characterised the American lunar quest of the 1960s. The focus of this thesis is on exploring historical and contemporary art and design depictions of the moon, with particular interest in the representation of lunacy and the visual reportage of the American lunar quest. The role of myth and the use of signifying visual codes in maintaining or departing from mythic archetypes is explored. Additionally the thesis investigates the communicative potential of infographics in raising awareness about the magnificent madness that was the American lunar quest. The research findings will be synthesised into a visual design that fuses moon landing facts with the myth of lunacy. This design will be targeted at an audience aged twenty to thirty.
Keywords: Contemporary art; Contemporary design; Representations of lunacy; Moon landing; Scientific rationalism; American space race; American lunar quest; Visual design; Myth of lunacy; Postmodern